2019
DOI: 10.3390/jcm8070950
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Fluctuation as a Risk Factor for Type 2 Diabetes: Results from a Nationwide Cohort Study

Abstract: We aimed to investigate how body weight fluctuation affects the risk of developing type 2 diabetes by conducting a nationwide cohort study. A total of 3,855,884 participants from the National Health Insurance System health check-up data from 2012 were included in this study, and follow-up continued until 2016. Body weight was measured at least thrice between 2009 and 2012. Body weight variability (BWV) was estimated using average successive variability (ASV) indices. Cox proportional hazards regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…A study evaluated the association Epidemiology/Health services research between variability in body weight and body weight gain or loss and reported the association between the variability in body weight and the development of diabetes. 13 However, the duration of this study was very short and the variability in body weight was calculated for the data of only 2-3 years. 13 The authors defined the weight-stable group with the change in body weight <±5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study evaluated the association Epidemiology/Health services research between variability in body weight and body weight gain or loss and reported the association between the variability in body weight and the development of diabetes. 13 However, the duration of this study was very short and the variability in body weight was calculated for the data of only 2-3 years. 13 The authors defined the weight-stable group with the change in body weight <±5%.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, the duration of this study was very short and the variability in body weight was calculated for the data of only 2-3 years. 13 The authors defined the weight-stable group with the change in body weight <±5%. 13 However, we consider that the ±5% change in body weight during 2-3 years was large and unstable.…”
Section: Discussionmentioning
confidence: 99%
“…83 Together, these results suggest that while weight out of 19 publications showed a positive correlation between weight cycling and increased body fat and deposition of AT centrally but did not find a correlation with increased risk of T2DM. Many other studies have seen a correlation between weight cycling and worsened cardiometabolic disease, atherosclerosis, and even mortality, [88][89][90][91] suggesting that it is still an important area of study.…”
Section: Wei G Ht Lossmentioning
confidence: 99%
“…Women who weight cycle appear to have a higher risk of diabetes than men who weight cycle, though few studies have focused on women. 33 In an analysis of over 3 million participants in the National Health Insurance Service in South Korea, weight fluctuation was assessed over three weights recorded over a 5-year period and new-onset diabetes was recorded over a 5-year follow-up period. Weight fluctuation was associated with a higher risk of new-onset diabetes (hazard radio [HR]: 1.10, 95% CI: 1.07-1.12) after adjusting for baseline BMI.…”
Section: Weight Cycling and Type 2 Diabetesmentioning
confidence: 99%